Pengaruh Model Pembelajaran Problem Based Learning, Efikasi Diri Dan Literasi Digital Terhadap Kemampuan Berpikir Kritis Siswa Kelas XI SMK Negeri 4 Surabaya - irda Fajriana; Rochmawati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This study aims to examine and analyze the effect of the Problem Based Learning (PBL) model, self-efficacy, and digital literacy on the critical thinking skills of 11th-grade students at SMK Negeri 4 Surabaya. This study employs a quantitative method with an ex post facto approach, which is used to investigate cause-and-effect relationships between variables that have already occurred without any data manipulation. The research sample consists of 84 students from the Financial Accounting Department, selected using the simple random sampling technique. Data were collected through questionnaires and analyzed using SmartPLS 4 with the Partial Least Square – Structural Equation Model (PLS-SEM) approach. The analysis process includes outer model testing to measure validity and reliability, inner model testing to examine the relationships between variables, and F-Square and R-Square tests to determine the magnitude of the independent variables' influence on the dependent variable.The findings indicate that Problem Based Learning, self-efficacy, and digital literacy each have a positive and significant effect on students' critical thinking skills. Among these factors, self-efficacy has the strongest influence. These three factors simultaneously contribute to enhancing students' critical thinking abilities in the Financial Accounting Department at SMK Negeri 4 Surabaya.